Kualitas Nata de pina dengan Pemberian Ekstrak Kecambah Kacang Hijau (Phaseolus radiata L.) yang diperlakukan dengan Air Cucian Beras dalam Perkecambahannya: The Quality of Nata de pina with the Application of Mung Bean Sprouts Extract (Phaseolus radiata L.) Treated with Rice Washing Water in Germination - Siti Khotimah; Rahmawati; Syarifah Risna Khairunisa (Life Science, 2025)
Nata de pina is a low-calorie organic food rich in fiber, made from pineapple juice (Ananas comosus L.). A supporting factor for the growth of Acetobacter xylinum (nata-forming bacteria) is a nitrogen source. The use of nitrogen sources such as non-food-grade zwavelzure ammoniak (ZA) is considered environmentally unfriendly, so an alternative solution is to use mung bean sprout extract as an organic nitrogen source. This study aims to determine the quality of nata de pina in terms of thickness, fiber content, color, texture, taste, and aroma with the application of mung bean sprout extract (Phaseolus radiata L.), which is treated with rice washing water during sprouting. Data analysis employed ANOVA and Duncan’s further test, with 7 treatment concentrations: control (0%), ZA 1%, mung bean sprout extract at 0.5%, 1%, 1.5%, 2%, and 2.5%. Each concentration was repeated 4 times. The nata layer formed on the fourth day and was harvested on the fourteenth day. The results showed that the best nata quality was obtained with a 1.5% mung bean sprout extract concentration, with a thickness of 1.09 cm, fiber content of 2.85%, and an organoleptic assessment with a score of 4 (like criteria). The resulting nata had a chewier texture, a fresh sour pineapple aroma, a yellowishwhite color, and a sweet taste. This study provides an effort to utilize pineapple juice waste and rice-washing water waste as potential raw materials for the development of healthy and environmentally friendly food products.